PEDATI Learning Design to Develop Asynchronous Online Learning Methods During the Covid-19 Pandemic - Mansur, Hamsi; Utama, Agus Hadi; Mastur; Sari, Noviana (2021 Universitas Riau International Conference on Education Technology (URICET), 2021)
The Covid-19 pandemic has resulted in the implementation of learning switching from face-to-face to virtual face-to-face and or online asynchronous. Online learning Asynchronous requires both teachers and students to be able to adapt to distance learning independently and collaboratively. However, one of the independent and collaborative learning strategies is the application of PEDATI learning designs to develop online learning methods asynchronous. PEDATI learning design is an abbreviation of PElajari - DAlami - Terapkan - evaluasI. This study aims to describe the application of PEDATI learning design to develop online learning methods asynchronous in elementary schools in Banjarmasin City. The subjects of this research are teachers and students who develop online learning methods asynchronous in elementary schools Central Banjarmasin District, while the object of this research is how to apply PEDATI learning designs into online learning methods asynchronous during the Covid-19 pandemic. The research method used is descriptive qualitative with primary data collection techniques are observations and interviews and secondary data sources are literature studies. Test the validity of the data by using the triangulation technique of data sources and extending the participation of informants. The data analysis technique used the Spradley braid analysis model. The results showed a positive response from partner institutions to participate in the participation extension program, seen from the effectiveness of the question-and-answer session between the instructor and training participants in the "very satisfied" category, as well as the content of Google Classroom virtual classrooms that had implemented PEDATI learning designs in the "eligible" category.